A new anatomical-functional model: effect of topiramate on capsaicin-induced mast cell degranulation in rat dura mater (Abstract) - Costa, Raisa Ferreira (Headache Medicine, 2022)
Dissertation (Master’s Degree in Biotechnology). Postgraduation in Biological Sciences. Federal University of Pernambuco, Recife, Brazil. 2020. 64 f. Supervisor: Prof. Dr. Marcelo Moraes Valença.